Toxicity of Nanomulsion of Castor Oil on the Fourth larval stage of Culex quinquefsciatus under Laboratory Conditions - Soolaf A Kathiar; Alla Abd Al Hassan Al Hilfy; Hazim Idan Al Shammari (مجلة بغداد للعلوم)
Mosquitoes like Culex quinquefasciatus are the primary vector that transmits many causes of diseases such as filariasis, Japanese encephalitis, and West Nile virus, in many countries around the world. The development in the scientific fields, such as nanotechnology, leads to use this technique in control programs of insects including mosquitoes through the use of green synthesis of nanoemulsions based on plant products such as castor oil.  Castor oil nanoemulsion was formulated in various ratios comprising of castor oil, ethanol, tween 80, and deionized water by ultrasonication. Thermodynamic assay improved that the formula of (10 ml) of castor oil, ethanol (5ml), tween 80 (14 ml) and deionized water (71ml)   was more stable than other formulas. The formulated castor oil nanoemulsion was characterized by transmitting electron microscopy and dynamic light scattering.  Nanoemulsion droplets were spherical in shape and found to have a Z-average diameter of 93 nm. A concentration of castor oil nanoemulsion (250, 350, 450, and 550 ppm) was tested as larvicidal agents and bulk emulsion (1000, 1500, 2000, and 2500 ppm) was tested also and compared against the fourth instar larvae. Our nanoemulsion showed higher activity when compared to bulk emulsion.   LC50 for castor oil nanoemulsion and castor bulk emulsion were found to be 268.21 and 409.37ppm after 72 h, respectively. The biochemical assays were carried out to examine the effect of castor oil nanoemulsion on biochemical characteristics of larvae. The treated larval homogenate showed inhibition in the activity of acetylcholinesterase.